IoT Smart Device for e-Learning Content Sharing on Hybrid Cloud Environment - Mohd. Yazid Idris; Deris Stiawan; Nik Mohd Habibullah; Abdul Hadi Fikri; Mohd Rozaini Abd Rahim; Massolehin Dasuki (IAES Indonesia Section, 2017)
Centralized e-Learning technology has dominated the learning ecosystem that brings a lot of potential usage on media rich learning materials. However, the centralized architecture has their own constraint to support large number of users for accessing large size of learning contents. On the other hand, Content Delivery Network (CDN) solution which relies on distributed architecture provides an alternative solution to eliminate bottleneck access. Although CDN is an effective solution, the implementation of technology is expensive and has less impact for student who lives in limited or non-existence internet access in geographical area. In this paper, we introduce an IoT smart device to provide e-Learning access for content sharing on hybrid cloud environment with distributed peer-to- peer communication solution for data synchronization and updates. The IoT smart device acts as an intermediate device between user and cloud services, and provides content sharing solution without fully depending on the cloud server.